AGROTECHNOLOGY OF MAIZE CULTIVATION - U. S. Saksonov; X. B. Buriev (Web of Journals Publishing, 2025)
This article provides information on soil preparation for maize cultivation, seed preparation for sowing, sowing periods and methods, maize grain and silage yield, fertilizer application rates, and irrigation regimes.
Keywords: Maize, grain, silage, irrigation regime, fertilizer application rates, seed.